Market Structure and Advance Selling - Marc Möller; Makoto Watanabe (Tinbergen Institute, 2016)
When products are sold in advance, i.e. prior to consumption, consumers trade off an early, uninformed purchase at a low price against a late, informed purchase at a high price. This paper considers the effect of market structure on the prevalence of advance selling. We show that in an oligopolistic market with multi-product firms, advance selling (with its associated allocative inefficiency) is decreasing in market concentration when the consumers' preference uncertainty is high but can be increasing when uncertainty is low.
Keywords: D43; D80; L13; 330; Competition; Price Discrimination; Individual Demand Uncertainty; Advance Purchase Discounts